Advanced electrode materials for Al on batteries - Pang, Jun Kai (Nanyang Technological University, 2020)
There are many electrode materials have been researched for aluminium-ion battery (AIB) in recent years except metal phosphorous trichalcogenides (MPX3). MPX3 has been proved to exhibit promising electrochemical performance in other rechargeable battery systems. As a result, a novel rechargeable aluminium ion battery has been fabricated with nanoparticle-liked copper phosphorus trichalcogenides (CuPS3) as cathode materials and ionic liquid electrolyte of AlCl3-[EMIm]Cl. An obvious charge and discharge voltage plateaus (1.8 V and 0.75 V vs Al/AlCl4-) during the first cycle is observed with a high specific capacity of 872 mAhg-1. Significantly, specific capacity of approximately 250 mAhg-1 with stable coulombic efficiency of around 90% is retained up to 53 cycles at a current density of 20 mAg-1. These meaningful results suggest potential of MPX3 application as cathode in AIB and represent a significant finding for the development of AIB.